The Influence of Macroeconomics Indicators to The Growth of Sukuk in Indonesia - Cupian, Cupian; Muasia, Rien; Putri, Safira Aryanti (EQUILIBRIUM, 2020)
The purpose of this study is to analyze the influence of macroeconomic on the growth of Islamic bonds (sukuk) in Indonesia period 2013.1-2016.12. This study uses Ordinary Least Square (OLS) method with a monthly time series starting from January 2013 until December 2016. The results of this study indicate that the Production Index (IP) and Bank Indonesia Syariah Certificate (BSBIS) variables positively and significantly affect the development of state sukuk issuance in Indonesia, then inflation negatively and significantly affects the development of state sukuk issuance, while the JII variable negatively and does not significantly affect the development of state sukuk issuance in Indonesia.